TINDAK PIDANA PENCURIAN DENGAN KEKERASAN (STUDI PUTUSAN NOMOR 92/PID/2021/PT.JAP) - Celine Wiranata; Vience Ratna Multiwijaya (Fakultas Hukum Universitas Trisakti, 2023)
The defendant, Otis Faskar Charkes Arera alias Otis, first committed violence by threatening the victim with a knife strapped around the victim's neck and in front of the victim's child. This threat was made in order to take the victim's property, which belonged to another person. Decision Study No. 92/PID/2021/PT Research Jap. The researcher poses the question: In light of Article 365, paragraphs 2 and 3, of the Criminal Code, are the actions of those who commit the crime of stealing with violence legitimate or not? This study employs a descriptive analytic normative research design and relies solely on secondary data, including main legal materials and secondary legal materials obtained from literature studies and analyzed qualitatively and then uses deductive logic in drawing conclusions. The conclusion of this study, namely that the actions of the perpetrators of the crime of theft with violence are inappropriate based on Article 365 paragraph (2) 1st and 3rd. Suggestions from this study, namely that investigators should in determining the article used as the basis must look at the facts based on Article 365 paragraph 1 in conjunction with paragraph 2 1st and 3rd of the Criminal Code.